Internal communication in the function of business success of digital media - Ljajić, Samir; Dojčinović, Milan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
The importance of efficient functioning of companies or media complexes is largely determined by internal and external communication. External communication factors concern the state of the market and the readiness for a certain corporation to market its products in the right way, that is, in the media context, contents in a purposeful and marketing efficient way. The subject paper discusses the factors of internal and external communication, with an apostrophe on internal communication in order to grow media companies and achieve business success, both from the perspective of marketing campaigns and from the perspective of market visibility of the media. Some of the issues discussed in the subject work concern the use of digital platforms for the purpose of better promoting media companies and marketing campaigns. The work of the "Južne vesti" portal was analyzed using the case study method, while the potential of the digital public sphere in the context of succsessful target advertise was illustrated through the example of the marketing campaign of the "Xiaomi" company.
Keywords: internal communication; digital media; information technology; media management; marketing